The Financially Fragile Firm: Is There a Case for It in the 1920s? - D. L. Isenberg (Levy Economics Institute of Bard College, 1989)
This paper is an empirical investigation of Minsky's hypothesis in the U.S. consumer durables sector during the 1920s. The first section of the paper briefly describes Minsky's financial fragility hypothesis, while the second sketches a brief economic historical background of the 1920s in the U.S. The third section introduces the methodology utilized and the fourth presents the results of the analysis. In the conclusion the findings and their implications are summarized.
Keywords: 330